Lysionotin induces apoptosis of hepatocellular carcinoma cells via caspase-3 mediated mitochondrial pathway. (1st August 2021) - Yang, Anhui; Zhang, Ping; Sun, Zhen; Liu, Xin; Zhang, Xinrui; Liu, Xingkai; Wang, Di; Meng, Zhaoli
Abstract: As the sixth most prevalent cancer, liver cancer has been reported as the second cause of cancer-induced deaths globally. Lysionotin, a ﬂavonoid compound widely distributed in Lysionotus pauciflorus Maxim, has attracted considerable attention due to its multiple biological activities. The present study analyzes the anti-liver cancer effects of lysionotin in cells and mouse models. In HepG2 and SMMC-7721 cells, lysionotin significantly reduced the viability of cells, inhibited cell proliferation and migration, enhanced cell apoptosis, promoted the increase of intracellular reactive oxygen species (ROS) levels, decreased mitochondrial membrane potential (MMP), and alternated the content of apoptosis-related proteins. In HepG2-and SMMC-7721-xenograft tumor mouse models, lysionotin inhibited tumor growth, reduced the expression levels of anti-apoptotic proteins and enhanced the expression levels of pro-apoptotic proteins in tumor tissues. Additionally, the pre-treatment of Ac-DEVD-CHO, an inhibitor of caspase-3, strongly restored the low cell viability, the enhanced apoptosis rate, the dissipation of MMP caused by lysionotin exposure, as well as prevented the lysionotin-caused enhancement on expressions of apoptosis related proteins, especially cleaved poly (ADP-ribose) polymerase (PARP), Fas Ligand (FasL), cleaved caspase-3 and Bax in both HepG2 and SMMC-7721 cells. Altogether, lysionotin showed significant anti-liver cancer effects related to caspase-3 mediated mitochondrial apoptosis. Highlights: Lysionotin induces apoptosis in liver cancer cells. Lysionotin causes the caspase-3 mediated mitochondrial apoptosis. Oxidative stress is involved in lysionotin-mediated mitochondrial apoptosis. Lysionotin regulates Nrf2 signaling to control oxidative stress. Lysionotin inhibits the growth of HepG2-and SMMC-7721-xenografted tumor.